Design and development of Indian tsunami detection system - Sudhakar, Tata; C. D, Suriyakala; Zacharia, Shijo (International Journal of Engineering and Technology, 2026)
India established first generation Tsunami Warning System in 2006. The first generation system was developed using indigenized data buoy technology and imported electronic systems. The second generation system is under development at National Institute of Ocean Technology, Chennai, India. This paper describes first generation system, design goals and novel system configuration of second generation system for Tsunami detection. It also reports indigenous second generation, laboratory testing and sea trial results. The Tsunami detection system may be enhanced redundancy.